2003
DOI: 10.1177/15648265030243s102
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Dosing of Micronutrients for Different Age Groups in the Life Cycle

Abstract: Many studies of micronutrient supplementation in developing countries have used single-nutrient supplements with either vitamins or minerals. However, people in these countries often suffer from multiple, rather than single, micronutrient deficiencies. The objective of this paper is to discuss the factors that go into determining the adequate dosing of vitamins and/or minerals for people of different ages. To elaborate on the adequacy of micronutrient doses in supplements, a model described by the US FNB was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Teenagers in the U.S. typically have energy-dense diets with poor micronutrient content [ 2 ]. Inadequate nutrient intake may be particularly detrimental for pregnant adolescents, who have greater nutritional requirements than their non-pregnant peers and pregnant adults because they must nourish not one but two growing bodies [ 3 , 4 , 5 , 6 ]. Previous studies have indicated that U.S. pregnant adolescents often do not meet the Institute of Medicine’s (IOM) recommendations for micronutrient intake [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Teenagers in the U.S. typically have energy-dense diets with poor micronutrient content [ 2 ]. Inadequate nutrient intake may be particularly detrimental for pregnant adolescents, who have greater nutritional requirements than their non-pregnant peers and pregnant adults because they must nourish not one but two growing bodies [ 3 , 4 , 5 , 6 ]. Previous studies have indicated that U.S. pregnant adolescents often do not meet the Institute of Medicine’s (IOM) recommendations for micronutrient intake [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough rationale for this formulation strategy was discussed at the Lima meeting, May 30-June 1, 2001, and is presented elsewhere in these proceedings by Bienz et al [6]. We formulated the foodLET with suitable overages to compensate for storage loss through the expected shelf life of the product and its use in the tropical environments of Vietnam and Indonesia.…”
Section: Nutrient Levelsmentioning
confidence: 99%
“…In 2001, the United States and Canada released the final versions of their reports on Dietary Reference Intakes (DRI), which included adequate intakes (AI) and tolerable upper limits (UL) [2]. The lessons learned from the DRI process have been skillfully teased out by Bienz et al [3] in relation to appropriate combinations of micronutrients for infants and toddlers. But North America is not the geographic stage for the endemicity of micronutrient malnutrition, begging the question as to whether the North American DRIs or the United Nations agencies' (World Health Organization, WHO; Food and Agriculture Organization, FAO) norms are applicable in terms of reference for developing societies.…”
Section: Highlights and Conclusion From The Workhopmentioning
confidence: 99%